2013
DOI: 10.1007/s00005-013-0218-1
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Roles of Neutrophils Via Opioid Peptides: Regulation of the Estrous Cycle and Pain

Abstract: Neutrophils are excreted into the vaginal vault at metestrus during the estrous cycle, and this phenomenon has long been used to determine the phase of the estrous cycle. A much smaller number of neutrophils are also detected in the uterus and the ovary. Recently, we provided several lines of evidence supporting the notion that neutrophils infiltrate into the ovary to regulate the estrous cycle by opioid peptides. Upon inflammation, on the other hand, neutrophils infiltrate into the site of infection to suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the oestrous cycle of mammalian therian females, oestrogen produced by the mature follicules initiates the phase of sexual receptivity (oestrus), whereas P4 production either assists with the progression of gestation or a period of inactivity (anoestrus) [24].…”
Section: Hormone Regulation Of the Reproductive Cycle -Introducing Thmentioning
confidence: 99%
See 1 more Smart Citation
“…In the oestrous cycle of mammalian therian females, oestrogen produced by the mature follicules initiates the phase of sexual receptivity (oestrus), whereas P4 production either assists with the progression of gestation or a period of inactivity (anoestrus) [24].…”
Section: Hormone Regulation Of the Reproductive Cycle -Introducing Thmentioning
confidence: 99%
“…© 2019 British Society for Immunology, Clinical and Experimental Immunology, 198:[24][25][26][27][28][29][30][31][32][33][34][35][36] …”
mentioning
confidence: 99%
“…The presence of infl ammatory cells in uterus tissue and in vaginal lavages seems to be directly related to the estrous cycle in female. During metaestrus, a number of neutrophils infi ltrate the vaginal cavity (Kobayashi 2013, Sasaki et al 2009). Neutrophil infi ltration into the vagina is critical in maintaining the cycle by controlling the levels of steroid hormones and angiogenesis via production of chemoattractants (Jiemtaweeboon et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that neutrophils in the ovary are divided into peripherally imported neutrophils and resident neutrophils [38]. However, neutrophils are less abundant in healthy ovaries [39,40]. Neutrophil phenotype is determined by surface markers and receptors as well as chemotaxis to different cytokines [34].…”
Section: Neutrophilsmentioning
confidence: 99%